Impact of discontinuing non-pharmacological interventions on cognitive impairment in dementia patients by COVID-19 lockdown. A pilot observational, longitudinal, retrospective study carried out in an adult day center in Spain during the COVID-19 pandemic - Sánchez-Valdeón, Leticia; Bello-Corral, Laura; Mayo-Iscar, Agustín; Fernández-Lázaro, Diego; Seco-Calvo, Jesús (Frontiers in Medicine, 2023)
Background: The lockdown imposed during the COVID-19 pandemic led to social isolation and prevented patients with dementia from receiving a suite of nonpharmacological interventions (NPIs) that prevent cognitive decline. This discontinuation of NPIs could substantially affect the mental health status of people with dementia in social care settings, such as adult day care centers (ADCs). Propose: The study aimed to evaluate the effects of the COVID-19 lockdown on mental health and cognitive impairment in patients with dementia who could not attend their usual ADCs and did not receive our NPIs, based on World Health Organization (WHO) Guidelines. Methods: Observational, longitudinal, retrospective study carried out in an adult day center in Spain We conducted a pilot cross-sectional study and reported it in accordance with the Strengthening Reporting of Observational Studies in Epidemiology (STROBE) statement. Cognitive status was assessed using the Mini-Mental State Examination (MMSE) in 80 patients attending the ADC of the " Leonese Association of Dementia Patients" (León, Spain), who had been evaluated with this instrument before the COVID-19 lockdown. The measures imposed during 3 months of lockdown have been associated with rapid worsening in cognitive decline in patients with dementia. Results: We observed a 0.4-point decrease in MMSE score/month (IQR=1.4) during lockdown versus a 0.1-point decrease/month (IQR=0.3) before this period (p=0.038). Notably, this translated to >10-point decreases in MMSE score/year in 33.8% of participants during lockdown versus 5.5% earlier (p<0.001). No statistically significant associations (p < 0.05) were found between the individual characteristics of the caregivers and the occurrence of the event. Conclusion: The reported declines in MMSE scores reveal a significant acceleration of cognitive decline during the period of inactivity. This could suggest that our NPIs, focused on slowing cognitive decline, are beneficial and, therefore, necessary in patients with dementia.